Start with the Street, the Voice Said. Issue 2 (4th May 2017) - Jobst, Marko
Abstract: This text offers a writing experiment that aims to address the processes of gentrification. It employs a narrative mode of writing in the first person plural in order to demonstrate one possible way of capturing the complexities of everyday experiences of metropolitan conditions. The text challenges the assumed notions of authorial voice and supposed analytical objectivity of (academic) critique and proposes a way of tackling the ambiguities that lie at the core of the relationship forged between urban subjects and objects that partake in the flows of capitalism. The accompanying photographs, while depicting some of the places described (Bermondsey Street in London, UK), are not literal illustrations. Readers are encouraged to forge their own connections.